Usulan Model Sistem Pengawasan Syariah Pada Perbankan Syariah Di indonesia - Ahmad Baehaqi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2014)
Supervision of Shariah compliance in the Islamic financial institutions is a DPS task This study analyzes and evaluates the compliance monitoring by taking the object of Islamic banking in Indonesia either approach or organizational systems approach. This study uses primary data in the form of interviews with 6 DPS on 6 BUS and secondary data from the report GCG 9 BUS 2011-2012. With inductive approach using content analysis and theoretical analysis, the results of this study indicate that the general practice of sharia compliance monitoring is still not optimal yet. Furthermore, this study proposes a model of supervision using a systems approach that aims to improve the supervision of such compliance. The model proposed in this study not only involve DPS, but also part of compliance, internal audit, and the audit committee of Islamic banking, as well as external audit and the Financial Services Authority (FSA) that acting as banking supervisor to replace BI.Supervision of Shariah compliance in the Islamic financial institutions is a DPS task This study analyzes and evaluates the compliance monitoring by taking the object of Islamic banking in Indonesia either approach or organizational systems approach. This study uses primary data in the form of interviews with 6 DPS on 6 BUS and secondary data from the report GCG 9 BUS 2011-2012. With inductive approach using content analysis and theoretical analysi, the results of this study indicate that the general practice of sharia compliance monitoring is still not optimal yet. Furthermore, this study proposes a model of supervision using a systems approach that aims to improve the supervision of such compliance. The model proposed in this study not only involve DPS, but also part of compliance, internal audit, and the audit committee of Islamic banking, as well as external audit and the Financial Services Authority (FSA) that acting as banking supervisor to replace BI.